The British school film: from Tom Brown to Harry Potter : representations of secondary education in British cinema - Glynn, Stephen (Palgrave Macmillan, 2016)
Intro -- Acknowledgements -- Contents -- List of Figures -- Part I: Introduction -- Chapter 1: The School Film: A British Genre? -- 1 Induction -- 2 Lessons in Genre -- 3 Lessons in Nationhood -- 4 School Reading List -- 5 Learning Objectives -- Notes -- References -- Part II: The Early Years Programme (1900-45) -- Chapter 2: The Early Public School Film (1900-1945) -- 1 First Years -- 2 Hitchcock and Co.: Down with School! -- 3 Hilton and Co.: Hurray for School! -- 3.1 Section Prize Winner: Goodbye, Mr. Chips (1939) -- 4 The Boys' Public School Carnivalesque -- 4.1 Section Prize Winner: Good Morning, Boys (1937) -- Notes -- References -- Part III: The Middle Years Programme (1945-70) -- Chapter 3: The Post-War Public School Film (1945-70) -- 1 The Right Stuff -- 1.1 Section Prize Winner: The Guinea Pig (1948) -- 2 The Wrong Woman -- 2.1 Section Prize Winner: The Browning Version (1951) -- 3 The Hay School -- 4 The Girls' Public School Carnivalesque -- 4.1 Section Prize Winner: The Happiest Days of Your Life (1950) -- 5 (Poetic) Realism and Tinsel -- 5.1 The Public School Film Victor Ludorum: If…. (1968) -- Notes -- References -- Chapter 4: The Post-War State School Film (1945-70) -- 1 The Right Stuff -- 2 The Wrong Woman -- 2.1 Section Prize Winner: Spare the Rod (1961) -- 3 Tinsel and Realism -- 3.1 The State School Film Victor Ludorum: Kes (1969) -- 4 Approved School -- 4.1 Section Prize Winner: The Loneliness of the Long Distance Runner (1962) -- Notes -- References -- Part IV: The Final Years Programme (1970-) -- Chapter 5: The Contemporary School Film (1970-) -- 1 Fright School -- 1.1 Section Prize Winner: Unman, Wittering and Zigo (1971) -- 2 Co-ed Carnivalesque (Mostly) -- 2.1 Section Prize Winner: Gregory's Girl (1981) -- 3 Queer School -- 3.1 Section Prize Winner: The History Boys (2006) -- 4 Approved and Special School.
https://katalog.adlr.link/Record/0-1656176637